2007
DOI: 10.1159/000108358
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aldose Reductase in the Peritoneal Changes of Patients Undergoing Peritoneal Dialysis

Abstract: Background/Aims: The mesothelium of patients undergoing peritoneal dialysis (PD) is exposed to glucose in dialysate. Glucose metabolites 3-deoxyglucosone and advanced glycation endproducts (AGEs) in the PD fluid induce peritoneal damage. Circulating factors also affect the peritoneum in the uremic model and predialysis patients. Aldose reductase (AR) generates precursors of 3-deoxyglucosone. We have reported AR acceleration in uremic patients. Therefore, AR acceleration might affect the peritoneum. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…The potential mechanism of AR involvement in drug resistance could be due to increased drug metabolism or increased efflux or decreased permeability of drugs from the cells [104]. Various studies in different cancer cells such as human stomach carcinoma cells, lung cancer and liver cancer, suggest that increased expression of AR contributes to carbonyl reduction and increased detoxification [105-107]. Lee et al [108] reported that overexpression of AR caused resistance to doxorubicin in liver cancer cells and inhibition of AR reversed the drug resistance.…”
Section: Role Of Ar In Carcinogenesismentioning
confidence: 99%
“…The potential mechanism of AR involvement in drug resistance could be due to increased drug metabolism or increased efflux or decreased permeability of drugs from the cells [104]. Various studies in different cancer cells such as human stomach carcinoma cells, lung cancer and liver cancer, suggest that increased expression of AR contributes to carbonyl reduction and increased detoxification [105-107]. Lee et al [108] reported that overexpression of AR caused resistance to doxorubicin in liver cancer cells and inhibition of AR reversed the drug resistance.…”
Section: Role Of Ar In Carcinogenesismentioning
confidence: 99%
“…Οι μθχανιςμοί επαγωγισ τθσ δράςθσ τθσ ALR2 ςε αυτζσ τισ περιπτϊςεισ δεν ζχουν μελετθκεί πλιρωσ αλλά πικανά περιλαμβάνουν εγκατάςταςθ οξειδωτικοφ ςτρεσ και ςυςςϊρευςθ ουραιμικϊν ουςιϊν και δικαρβονυλικϊν παραγϊγων. Θ επαγωγι τθσ δράςθσ τθσ ALR2, τουλάχιςτο εν μζρει, επθρεάηει τθν μεμβράνθ του περιτόναιου ςε αςκενείσ που υποβάλλονται ςε αιμοκάκαρςθ (Hasuike et al, 2007). Σε αυτζσ τισ περιπτϊςεισ βλαβϊν τθσ μεμβράνθσ του περιτόναιου με μορωολογικζσ αλλοιϊςεισ παρατθρείται μειωμζνθ λειτουργικότθτα, όπωσ για παράδειγμα απϊλεια τθσ ςπειραματικισ διικθςθσ.…”
Section: Alr2 and νεφρικέσ δυςλειτουργίεσunclassified